(untitled) (Research, Society and Development, 2021)
Objective: The main purpose of this paper was to evaluate the incidence of Ventilator-Associated Pneumonia (VAP) in an Intensive Care Unit (ICU) and the adherence of the bundles by healthcare professionals. Methodology: This study was prospective, observational, and quantitative, performed in an ICU located in Ponta Grossa (Paraná, Brazil) gathering data from December 2018 to February 2019 through medical records and bedside observations. Results: This study included 56 patients, of whom 3 acquired VAP. The multi-professional team performed several procedures that met the prevention bundles in that UCI, writing them down in medical records, but some of them were not being applied in practice or were not performed properly, exposing divergences between annotations and bedside observations. Conclusion: It is noted that bundles are effective in preventing VAP, reduces risks of HAI and, consequently, deaths. However, there is a need to guide the applicability and registration by the multidisciplinary team, optimizing the adherence of these measures, in order to improve the quality of health of patients and reducing costs and the length of stay in the ICU related to VAP.